PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI UKM PERINDUSTRIAN DAN PERDAGANGAN PROVINSI PAPUA BARAT DAYA - Way, Yonas; Irwan, Andi; Anwar, Vebby (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of work motivation and job satisfaction on employee performance at the Office of Cooperatives, SMEs, Industry, and Trade of Southwest Papua Province. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to employees of the relevant office. The results showed that partially, work motivation had a significant effect on employee performance, indicating that increased work motivation can encourage employees to work more optimally in carrying out their duties and responsibilities. Furthermore, job satisfaction was also proven to have a significant effect on employee performance, indicating that levels of satisfaction with their jobs, work environment, and rewards play a crucial role in improving performance. Simultaneously, the F-test results indicated that work motivation and job satisfaction jointly had a significant effect on employee performance at the Office of Cooperatives, SMEs, Industry, and Trade of Southwest Papua Province. This finding confirms that employee performance is not influenced by a single factor in isolation but rather results from the interaction of various mutually supportive internal factors.